2003
DOI: 10.1074/jbc.m211448200
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein-1 (BMP-1)

Abstract: Bone morphogenetic protein-1 (BMP-1) is a shorter spliced variant of mammalian tolloid (mTld), both of which cleave the C-propeptides of type I procollagen during the synthesis of extracellular matrix collagen fibrils. The fact that BMP-1 and mTld both exhibit procollagen C-proteinase (PCP) activity and that BMP-1 is the smaller variant might indicate that BMP-1 comprises the minimal required sequences for PCP activity. BMP-1 comprises a metalloproteinase domain, three CUB domains, and an epidermal growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 22 publications
3
48
3
Order By: Relevance
“…NotI sites were introduced by PCR at the borders of the EGF domain of the cDNA clone, and restriction enzyme digestion was used to delete individual domains. Previous work showed that the NotI-derived alanine residues had no effect on the procollagen C-proteinase activity of BMP-1 when inserted at the domain junctions (20). The recombinant proteins contained a V5-peptide epitope at the C terminus to facilitate Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…NotI sites were introduced by PCR at the borders of the EGF domain of the cDNA clone, and restriction enzyme digestion was used to delete individual domains. Previous work showed that the NotI-derived alanine residues had no effect on the procollagen C-proteinase activity of BMP-1 when inserted at the domain junctions (20). The recombinant proteins contained a V5-peptide epitope at the C terminus to facilitate Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Site-directed Mutagenesis-Deletion of the EGF-like domain 1 was as described (20). The ⌬EGF1-BMP-1 clone was used to generate the His-tagged mTld-⌬EGF1 mutant, by excising and re-cloning the fragment comprising the deletion by BamHI (position 1390) and AviII (position 1954).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations